Community participation as a way for empowerment in charge of the Comedores Comunitarios program in Culiacán, México - Verdugo-Araujo, Luz Mercedes; Tereso-Ramírez, Leonor; Carrillo-Montoya, Teresita del niño Jesús (Prospectiva. Revista de Trabajo Social e Intervención Social, 2019)
The article analyzes the experience of women implementing a social program that aims to reduce hunger. They have become mediators of the locality, being the link between the institutional apparatus and the beneficiaries. They have also positioned themselves as protagonists in the community and, although they have managed to reach a certain degree of empowerment through community participation, in the political arena, there are circumstances that limit their full development. The objective of this work is to reflect about the construction of the process of empowerment that is generated in the daily life of the female leaders of the Comedores Comunitarios program, identifying their political, social and cultural strategies as a result of their social action. The methodological route is based on a hermeneutic-interpretative analysis that emerges from the discourse of 27 women who operate the community dining program in the municipality of Culiacán, in the State of Sinaloa, Mexico.We conclude that empowerment is not something that can be given to another person, but rather an individual process of self-confrontation and self-questioning regarding the situation that each person finds him/herself in within the community.